Proposal for the implementation of Lean Manufacturing tools in an automation company, Trujillo-Peru, 2020 [Propuesta de implementación de herramientas de Lean Manufacturing en una empresa de automatización, Trujillo-Perú, 2020] - Gómez-Cárdenas, María Fe (2021)
The competitive market in which industries operate requires them to evaluate their processes and develop strategies focused on product improvement, production processes and customer service. The objective of this research was to determine to what extent the Lean Manufacturing tools implementation proposal would increase the productivity of an automation company in the city of Trujillo-Peru, 2020. In this sense, an initial diagnosis was made to the company identifying as main problems: the accumulation of damaged items in the warehouse, unproductive times due to unnecessary movements, orders delivered out of time to the customer and reprocesses due to inadequate work procedures. The implementation proposal consisted of the development of Lean Manufacturing tools: 5S, Kanban, Systematic Layout Planning and PDCA. According to the proposal made, productivity could be improved by 24.99% and an economic benefit of S/66,112.52 per year could be obtained. In addition, the financial analysis of the proposal was carried out, obtaining a NPV of S/12,786.22, an IRR of 50% and a benefit–cost ratio of 2.71, which indicated the feasibility of the proposal.